2004
DOI: 10.1080/aan.50.2.121.129
|View full text |Cite
|
Sign up to set email alerts
|

Use of Atomic Force Microscopy to Reveal Sperm Ultrastructure in Hiv-Patients on Highly Active Antiretroviral Therapy

Abstract: Atomic force microscopy (AFM) has been employed to examine morphological and topographical changes caused by human immunodeficiency virus (HIV) and the effects of highly active antiretroviral therapy (HAART) on spermatozoon of HIV infected patients. This powerful technique has allowed us to visualize morphological alterations present in the spermatozoa of patients either with or without treatment. In addition to this, even the minute details, such as viral particles, located on the membrane of the spermatozoa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 11 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Although RDs are part of HIV complications widely reported in the literature before introducing highly active antiretroviral therapy (HAART) 2 , 3 . Nevertheless, the roll-out of HAART since the mid-80s and to date, antiretroviral therapy is now perceived as a direct or indirect cause of RDs via various mechanisms of action 4 , 5 . Among several adverse effects of HAART are insulin resistance and type 2 diabetes mellitus (T2DM), which were documented as HIV-1 therapeutic detrimental effects, especially HAART 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Although RDs are part of HIV complications widely reported in the literature before introducing highly active antiretroviral therapy (HAART) 2 , 3 . Nevertheless, the roll-out of HAART since the mid-80s and to date, antiretroviral therapy is now perceived as a direct or indirect cause of RDs via various mechanisms of action 4 , 5 . Among several adverse effects of HAART are insulin resistance and type 2 diabetes mellitus (T2DM), which were documented as HIV-1 therapeutic detrimental effects, especially HAART 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar clinical cohort and in vivo studies have documented a deleterious effect of TDF on semen and sperm indices such as count, motility, and morphology [ 45 – 47 ]. Previous studies have implicated highly active antiretroviral therapy in various reproductive perturbations such as a significant decrease in sperm count, alteration to spermatozoa, and increased abnormal sperm forms [ 48 , 49 ]. All these findings taken together, indicate the adverse effect of TDF on sperm indices and morphology.…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that spermatozoa damage was due to antiretroviral drug exposure, and not the result of the HIV virus itself. 63 The impact of antiretroviral drugs on the fertility of female adults is more complex. In adult women living with HIV, low mitochondrial DNA levels in oocytes, a dysfunction typically associated with infertility, has been reported.…”
Section: Cart and Changes In Pregnancymentioning
confidence: 99%